2016
DOI: 10.1016/j.robot.2015.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Pose estimation-based path planning for a tracked mobile robot traversing uneven terrains

Abstract: A novel path-planning algorithm is proposed for a tracked mobile robot to traverse uneven terrains, which can efficiently search for stability sub-optimal paths. This algorithm consists of combining two RRT-like algorithms (the Transition-based RRT (T-RRT) and the Dynamic-Domain RRT (DD-RRT) algorithms) bidirectionally and of representing the robot-terrain interaction with the robot's quasi-static tip-over stability measure (assuming that the robot traverses uneven terrains at low speed for safety). The robot'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
(96 reference statements)
0
13
0
1
Order By: Relevance
“…So, a set Θ * P ⊆ Θ P is -stop only if ∀θ 1 , θ 2 ∈ Θ * P , θ 1 = θ 2 , box(θ 1 ) = box(θ 2 ) and box(θ 1 ) ⊀ box(θ 2 ). (9) Thus, a Θ * P is reached with the greatest possible number of solutions that adequately characterize Pareto's front and whose number of possible solutions depend on n_box i , and will not exceed the following level.…”
Section: Multiobjetive Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…So, a set Θ * P ⊆ Θ P is -stop only if ∀θ 1 , θ 2 ∈ Θ * P , θ 1 = θ 2 , box(θ 1 ) = box(θ 2 ) and box(θ 1 ) ⊀ box(θ 2 ). (9) Thus, a Θ * P is reached with the greatest possible number of solutions that adequately characterize Pareto's front and whose number of possible solutions depend on n_box i , and will not exceed the following level.…”
Section: Multiobjetive Optimizationmentioning
confidence: 99%
“…Autonomous vehicles with non-holonomic characteristics [6][7][8] can be technologically adapted to different environments, and so, produce unmanned ground vehicles (UGVs) [9][10][11], unmanned underwater vehicles (UUVs) [12][13][14], and unmanned aerial vehicles (UAVs) [15][16][17][18]. Obviously, each of the above categories presents its own scientific and technological challenges, including path planning, navigation, and guidance.…”
Section: Introductionmentioning
confidence: 99%
“…The terrain settling technique is used in the current ground operation of Mars rovers to check safety before sending mobility commands (Wright et al, ; Yen, Cooper, Hartman, Maxwell, & Wright, ). The kinematic settling is also effective for other types of vehicles, such as tracked vehicles (Jun, Saut, & Benamar, ). The kinematics approach is generally faster than dynamics‐based approach, but still computationally demanding for onboard execution on spacecraft computers.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the method was fast enough for real-time operation. Jae-Yun Jun [25] proposed a novel path-planning algorithm as a tracked mobile robot to traverse uneven terrains, which could efficiently search for stability sub-optimal paths. The method demonstrated that the proposed algorithm could be advantageous over its counterparts in various aspects of the planning performance.…”
Section: Introductionmentioning
confidence: 99%